Estudio comparativo del nivel de agresividad por sexo en estudiantes de la Escuela de Educación Básica General Juan Lavalle - Gavin Guzñay, Allison Mishell (2021)
The purpose of this research work was to compare the levels of aggressiveness by gender that exist in Elementary Education students at “Juan Lavalle” General Basic Education School, this work was carried out with a non-probabilistic sample made up by 82 students of the Tenth Year courses of General Basic Education, (EGB for its acronym in Spanish, this research was approached from the psychological point of view applying the psychometric technique in which the Questionnaire of Premeditated and Impulsive Aggression in Adolescents (CAPI-A for its acronym in Spanish) was used in order to know the levels of aggressiveness of women and men, according to the results obtained from the questionnaires applied to students indicate that most of women and men do not present levels of aggressiveness or, in turn, these levels are not yet defined. However, a small group of adolescents, men and women, have a predominance at the level of impulsive aggressiveness in which women belong to the group with the greatest presence of this level of aggressiveness, in which their behavior is explosive and it is manifested directly and actively, on the other hand, male adolescents present a level of premeditated aggressiveness, but it is necessary to mention that this level of aggressiveness is more manifested in women, since these adolescents use aggressiveness for their own good. Finally, a minority of men present a mixed level, in other words, between the two levels, certain behaviors of impulsive and premeditated aggressiveness are combined, on the other hand, women do not present this level of mixed aggressiveness.